Structure activity studies of truncated latrunculin analogues with anti-malarial activity - Varghese,S; Rahmani,R; Drew,DR; Beeson,JG; Baum,J; Smith,BJ; Baell,J (ChemMedChem, 2021)
Malarial parasites employ actin dynamics for motility, and any disruption to these dynamics renders the parasites unable to effectively establish infection. Therefore, actin presents a potential target for malarial drug discovery, and naturally occurring actin inhibitors such as latrunculins are a promising starting point. However, the limited availability of the natural product and the laborious route for synthesis of latrunculins have hindered their potential development as drug candidates. In this regard, we recently described novel truncated latrunculins, with superior actin binding potency and selectivity towards P. falciparum actin than the canonical latrunculin B. In this paper, we further explore the truncated latrunculin core to summarize the SAR for inhibition of malaria motility. This study helps further understand the binding pattern of these analogues in order to develop them as drug candidates for malaria.